Communities in the stalls: A study of latrinalia linguistic landscapes. Issue 2 (3rd April 2019) - Amevuvor, Jocelyn; Hafer, Greg
ABSTRACT: Latrinalia consists of pictures and messages written on bathroom stalls (Dundes, 1966). Much of the research on latrinalia has focused on how people using men's and women's restrooms constructed those restrooms differently (Arluke, Kutakoff, & Levin, 1987; Bartholome & Snyder, 2004; Dundes, 1966; Kinsey et al., 1998). The authors look at latrinalia as a linguistic landscape and hone in on how the constructed spaces reflect the larger context of the university they are situated in by examining how the latrinalia may relate to broader social issues. In addition, the authors investigate the ways in which men and women constructed their spaces differently, with men having more sexually explicit latrinalia and women's restrooms having more encouraging latrinalia.